The Relevance of Metacognitive Skills to Autonomous Language Enrichment - Suchanova, Jelena (Acta Paedagogica Vilnensia, 2006)
University students need to know a foreign language comprehensively. The acquisition and enriching a foreign language vocabulary is one of the essential part of it. Unfortunately, the restrictions imposed by the curricula often do not meet the actual needs of the students. Moreover, the recent research shows that students are not able to use their metacognitive skills that would allow them to be able to master their foreign language vocabulary autonomously. Teachers often teach the way they were taught rather than consider the advantages and disadvantages of alternative approaches and how to use them most effectively. The author suggests using Cognitive Apprenticeship method as means of promoting metacognitive skills in acquisition new foreign language vocabulary. The development and ability to manage metatacognitive skills will enable students to become autonomous.
Keywords: university; students; teaching; metacognitive skills; language enrichment